Development And Perfomance Of Cogeneration Biomass Stove Integrated With Thermoelectric Generator (Teg) - Manivelu, Vishnuwaaran (Universiti Sains Malaysia, 2017)
The usage of biomass stoves is all over the place in rural area of developing countries. It is essential to use all the available resources without letting it go waste such as the waste heat from the stove. A rocket stove has been developed at USM for cooking. The stove has been designed to be smokeless and high efficient stove. But the wall of the stove is still hot and heat is lost to the surrounding. Small scale independent electrical generator for home usage such as charging phone, tab and laptop is not available. This is a need to develop a small scale power generator based on rocket stove which dedicated for power generation. So, two upgraded cogeneration biomass stoves with different purposes has been developed in our workshop and prototypes have been built. One stove focuses on better performance of cooking, and at the same time generating power. Another stove focuses on better performance of power generation, and can use for cooking at the same time. A module called thermoelectric generator (TEG) has integrated with the stove in order to generate electricity from the waste heat to power the basic electric equipment. This paper discusses the data obtained from the experiment using commercial TEG compare with the theoretical data for both stoves. Lastly, two different experimental set up using the TEG and the stoves is presented showing that TEGs generate 2.15W and 4.69W power from each stove and ready to be used as possible power generator at rural area.